Simultaneous Determination of Parathion, Malathion, Diazinon, and Pirimiphos Methyl in Dried Medicinal Plants Using Solid-Phase Microextraction Fibre Coated with Single-Walled Carbon Nanotubes. (2nd May 2012) - Ahmadkhaniha, Reza; Samadi, Nasrin; Salimi, Mona; Sarkhail, Parisa; Rastkari, Noushin
Abstract : A reliable and sensitive headspace solid-phase microextraction gas chromatography-mass spectrometry method for simultaneous determination of different organophosphorus pesticides in dried medicinal plant samples is described. The analytes were extracted by single-walled carbon nanotubes as a new solid-phase microextraction adsorbent. The developed method showed good performance. For diazinon and pirimiphos methyl calibration, curves were linear (r 2 ≥ 0.993 ) over the concentration ranges from 1.5 to 300 ng g − 1, and the limit of detection at signal-to-noise ratio of 3 was 0.3 ng g − 1 . For parathion and malathion, the linear range and limit of detection were 2.5–300 (r 2 ≥ 0.991 ) and 0.5 ng g − 1, respectively. In addition, a comparative study between the single-walled carbon nanotubes and a commercial polydimethylsiloxane fibre for the determination of target analytes was carried out. Single-walled carbon nanotubes fibre showed higher extraction capacity, better thermal stability (over350 ∘ C), and longer lifespan (over 250 times) than the commercial polydimethylsiloxane fibre. The developed method was successfully applied to determine target organophosphorus pesticides in real samples.